Route and type of nutrition influence mucosal immunity to bacterial pneumonia. - King, B K (1999)
OBJECTIVE: To develop a model of established respiratory immunity against Pseudomonas aeruginosa pneumonia and to investigate the effects of route and type of nutrition on this immunity. SUMMARY BACKGROUND DATA: Diet influences the ability of gut-associated lymphoid tissue (GALT) to maintain mucosal immunity. Complex enteral diets and chow maintain normal GALT populations against established IgA-mediated antiviral respiratory immunity. Both intravenous and intragastric total parenteral nutrition (TPN) produce GALT atrophy, but only intragastric TPN preserves established antiviral immunity. The authors hypothesized that both GALT-depleting diets (intragastric and intravenous TPN) would impair immunity against bacterial pneumonia. METHODS: P. aeruginosa was administered intratracheally to determine the mortality rate at increasing doses, and liposomes containing P. aeruginosa antigens were used to generate effective respiratory immunization. In the final experiment, mice received liposomes containing P. aeruginosa antigens to establish immunity and then were randomized to chow, complex enteral diets, intragastric TPN, or intravenous TPN. After 5 days of diet, mice received live intratracheal P. aeruginosa, and the death rate was recorded at 24 and 48 hours. RESULTS: The LD50 and LD100 were 9 x 10(7) and 12 x 10(7), respectively. Immunization reduced the mortality rate from 66% to 12%. This immunization was maintained in mice fed chow or a complex enteral diet and was lost in animals receiving intravenous TPN. Intragastric TPN partially preserved this respiratory immunity. CONCLUSIONS: Protection against bacterial pneumonia can be induced by prior antigenic immunization. This protection is lost with intravenous TPN, partially preserved with a chemically defined enteral diet, and completely preserved with chow or complex enteral diets. Both route and type of nutrition influence antibacterial respiratory tract immunity.